Designing a Folklore Storybook Entitled "Sang Kridesan" as a Cultural Heritage of Prabumulih - Felicia, Fara; Yusri; Sunani (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2023)
The purpose of this research is to design a folklore storybook entitled "Sang Kridesan" as a cultural heritage of Prabumulih folklore. The research method used to produce the storybook was Research & Development method that modified by Sukmadinata which consisted of 3 steps (1) Preliminary Study , (2) Model/Product Development, and (3) Final Product Testing and Dissemination. There were two kinds of data collected : Primary data which were collected from field survey, from the experts or the reviewers, from the respondents in limited testing step, and from the respondents in wider testing step and secondary data which were collected from the library on the step of the literature study. In preliminary study, the writer conducted three steps, they were literature study, field survey, and arranging model/product draft. In Model Development step, the writer conducted limited testing, wider testing, and final product testing by involving the experts in the content, the language, the storybook designing, and the storybook writing. Keywords: Designing, Folklore, Storybook, Cultural Heritage